As imagens poéticas do delírio : um estudo da obra Paranoia de Roberto Piva - Brito, Rodrigo Fernandes Ferreira (2016)
This research was based on the book of Roberto Piva, a poet from São Paulo, Brasil, who was very fond of surrealism and the Beat Generation, and whose photographs were taken by the photographer Wesley Duke Lee, with the purpose of expanding the aesthetic experience of reading. Freudian-Lacanian psychoanalysis is the main approach of the research in order to understand the issues or tensions of the book. The study is divided into two parts. In chapter one, it was necessary to contextualize the book in the Brazilian literature, mainly the surrealistic poetry characteristics and the Beat characteristics in the country. Some authors, like Valéry, Barthes, Kristeva, Mariguela, and Agamben, are mentioned in order to obtain the connection of literature and Psychoanalysis, so the writing may be the main point between the psychic automatism and the dream contents which enables opening the unconscious side. São Paulo, the city where you may listen to lyrical voices, is presented in the poems from scenes of a possible hostile life in the Brazilian metropolis, which unfolds the poetry of Piva as Baudelaire‟s modern. According to Friedrich, the french poet found in the city that the decadent, the miserable, the bad and the dark sides are poetic subjects. It is in this perspective that the look of selflyrical designs the conflicting images of a city on the verge of ruins. In chapter two, some poems and a photograph were selected for the analysis of the Critical-Paranoid Method that Salvador Dali theorized. We noticed the derogatory and decadent references to the human body on the poems, which had significant roles in the analysis because they have audio-visual games which refer to the Dalian method. The sense effect produced by the audio-visual details was considered by Žižek as the main object of desire. Therefore, it was essential for deeper understanding of synesthesia, alliteration, metaphors and other aspects of the language that appear in the form of dissonant elements of the poems and photography that make up this artwork.